2021
DOI: 10.1111/jfpp.15188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermittent drying on the energy consumption and physiological quality of soybean seeds

Abstract: mental crises that are approaching and progressing today are the result of intensified industrial development-including climate change (global warming, greenhouse gases, etc.,), air pollution, and water issues (Nawi et al., 2016). In this context, scientists and studies are increasingly focusing on energy efficiency and reliability policies (Unver & Kara, 2019), in order to develop the alternative methods that contribute to the reduction of energy consumption. Drying is one of the oldest and most important way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Drying condition Heat saving (%) Reference Barley T = 20-25 C 2 9 -44 (Carvalho et al, 2021) Camellia oleifera seeds T = 40-80 C 29.3 (Huang et al, 2020) Corn grains T = 23-36 C 6.1 (Silva et al, 2020) Corn seeds t = 0-20 h 70 (Xie et al, 2020) Green soybeans Seeds t = 0-550 min 53 (Zhao et al, 2017) Paddy grains T = 35-55 C 59 (Mehran et al, 2019) Red beetroot T = 25-85 C 5 0 -75 (Szadzinska et al, 2020) Rough rice grains T = 40 and 70 C 6 8 -72 (Franco et al, 2020) Soybean seeds T = 50 and 70 C 4 2 -46 (Bissaro et al, 2020)…”
Section: Methodsmentioning
confidence: 99%
“…Drying condition Heat saving (%) Reference Barley T = 20-25 C 2 9 -44 (Carvalho et al, 2021) Camellia oleifera seeds T = 40-80 C 29.3 (Huang et al, 2020) Corn grains T = 23-36 C 6.1 (Silva et al, 2020) Corn seeds t = 0-20 h 70 (Xie et al, 2020) Green soybeans Seeds t = 0-550 min 53 (Zhao et al, 2017) Paddy grains T = 35-55 C 59 (Mehran et al, 2019) Red beetroot T = 25-85 C 5 0 -75 (Szadzinska et al, 2020) Rough rice grains T = 40 and 70 C 6 8 -72 (Franco et al, 2020) Soybean seeds T = 50 and 70 C 4 2 -46 (Bissaro et al, 2020)…”
Section: Methodsmentioning
confidence: 99%
“…In soybean grains, the drying intermittency, combined with temperatures below 40°C, minimizes physical damage to the products, mainly by reducing the grain thermal and moisture stress (Jung & Yoon, 2018). Moreover, a study showed that the application of intermittence at a drying temperature of 70°C reduces the process energy consumption by approximately 46% (Bissaro et al, 2020). Consequently, other process variables, such as drying time, are determining factors for the process performance.…”
Section: Drying Technologymentioning
confidence: 99%
“…Moreover, a study showed that the application of intermittence at a drying temperature of 70 C reduces the process energy consumption by approximately 46% (Bissaro et al, 2020). Consequently, other process variables, such as drying time, are determining factors for the process performance.…”
Section: Drying Technologymentioning
confidence: 99%